2023
DOI: 10.3390/foods12091762
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Soy Bread Intervention Leads to a Dose-Response Increase in Urinary Isoflavone Metabolites and Satiety in Chronic Pancreatitis

Abstract: Patients with chronic pancreatitis (CP) are particularly vulnerable to nutrient malabsorption and undernutrition caused by the underlying pathology of their disease. Dietary intervention trials involving soy isoflavones in patients with CP are limited and isoflavone metabolites have not yet been reported. We hypothesized soy bread containing plant-based protein, dietary fiber, and isoflavones would be well-tolerated and restore gut functional capacity which would lead to isoflavone metabolites profiles like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Whereas the degree of equol metabolism depends on various factors, dietary habits are one of the important factors leading to differences in intestinal microbiota. It is reported that only 25–30% of young people in Western countries produce equol after eating foods containing soy [ 43 ], which is significantly lower than the 50~60% equol productivity reported in Asian countries such as China, Korea, and Japan [ 44 , 45 ], or Western vegetarianism [ 46 ]. At the same time, the host’s intestinal microbiota, lifestyle, and genetic factors affect the production of equol; however, equol production is still determined by: (1) specific equol-producing bacteria, (2) the source of substrate derived from daidzein, and (3) an intrinsic environment capable of providing redox for the reaction to occur.…”
Section: Production Methods Of Equolmentioning
confidence: 99%
“…Whereas the degree of equol metabolism depends on various factors, dietary habits are one of the important factors leading to differences in intestinal microbiota. It is reported that only 25–30% of young people in Western countries produce equol after eating foods containing soy [ 43 ], which is significantly lower than the 50~60% equol productivity reported in Asian countries such as China, Korea, and Japan [ 44 , 45 ], or Western vegetarianism [ 46 ]. At the same time, the host’s intestinal microbiota, lifestyle, and genetic factors affect the production of equol; however, equol production is still determined by: (1) specific equol-producing bacteria, (2) the source of substrate derived from daidzein, and (3) an intrinsic environment capable of providing redox for the reaction to occur.…”
Section: Production Methods Of Equolmentioning
confidence: 99%